Enhanced biomass productivity of Arthrospira platensis using zeolitic imidazolate framework-8 as carbon dioxide adsorbents. (December 2019) - Cheng, Jun; Zhu, Yanxia; Xu, Xiaodan; Zhang, Ze; Yang, Weijuan
Graphical abstract: Schematic of CO2 fixation by microalgae cells. (a) most CO2 released into atmosphere without ZIF-8; (b) zeolite imidazolate framework ZIF-8 as CO2 adsorbents promoted CO2 gas conversion into HCO3 – dissolved in solution and microalgae growth rate. Notes: Chl a, rETR and BP represented chlorophyll a concentration, relative electron transport rate and biomass productivity, respectively. Highlights: ZIF-8 as adsorbent improved CO2 conversion to HCO3 – by 72.9% to culture A. platensis. The increased c[HCO3 – ] facilitated thylakoid membrane to activate photosynthesis. The biomass productivity of A. platensis cultured with ZIF-8 increased by 64.0%. Abstract: In order to improve CO2 diffusion in algae solution and conversion into dissolved HCO3 –, zeolitic imidazolate framework-8 (ZIF-8) with zinc cores as unsaturated metal sites was first used as CO2 adsorbents. Flue gas CO2 from coal-chemical industry can be adsorbed and can be made available throughout cultivation to promote biomass productivity of Arthrospira platensis . The ZIF-8 adsorbent with particle size of 719 nm performed the largest pore area of 351.8 m 2 /g, which promoted CO2 conversion into HCO3 – by 72.9% compared to control condition without ZIF-8. The increased HCO3 – concentration enhanced thylakoid membrane proportion in cell cross-sectional area by 1.3 times to 78.3%, which resulted in enhancement of photosynthesis in A. platensis cells. Relative electron transport rate increased by 9.4% accordingly, which was attributed to the improvement of chlorophyll a concentration by 110%. The biomass productivity using ZIF-8 adsorbent with particle size of 719 nm markedly increased by 64.0%.